Exploring Elementary Students’ Mathematical Reasoning through Patterns and Geometric Shapes: A Case Study at MI Salamah, Jambi City - Milla Rodhiana Rasyid; Rohati Rohati; Duano Sapta Nusantara (MASI Mandiri Edukasi, 2026)
This study examined the mathematical reasoning abilities of elementary students at MI Salamah, in Jambi City, on the topics of patterns and geometric figures. The research was motivated by the limited number of studies that explore students’ real-time reasoning processes in elementary geometry contexts. The study aimed to describe how students with different ability levels demonstrate mathematical reasoning when solving pattern and geometry problems. A descriptive qualitative method was applied, involving three purposively selected fifth-grade students representing high, medium, and low ability levels. Data were collected through two open-ended reasoning tasks developed based on four indicators: making conjectures, performing mathematical manipulations, providing justification, and drawing conclusions. The findings revealed clear variations in students’ reasoning abilities: high-ability students demonstrated logical reasoning but had difficulty generalizing patterns; medium-ability students showed partial conceptual understanding with inconsistent justifications; and low-ability students relied on guessing without coherent reasoning. These results indicate that students tended to depend on procedural thinking rather than conceptual reasoning. The study contributes to understanding the developmental shift from procedural to conceptual reasoning and offers implications for designing instructional activities that strengthen reasoning in elementary mathematics learning.